2005
DOI: 10.1128/mcb.25.6.2297-2309.2005
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interstrand Cross-Link Repair in theSaccharomyces cerevisiaeCell Cycle: Overlapping Roles forPSO2(SNM1) with MutS Factors andEXO1during S Phase

Abstract: Pso2/Snm1 is a member of the ␤-CASP metallo-␤-lactamase family of proteins that include the V(D)J recombination factor Artemis. Saccharomyces cerevisiae pso2 mutants are specifically sensitive to agents that induce DNA interstrand cross-links (ICLs). Here we establish a novel overlapping function for PSO2 with MutS mismatch repair factors and the 5-3 exonuclease Exo1 in the repair of DNA ICLs, which is confined to S phase. Our data demonstrate a requirement for NER and Pso2, or Exo1 and MutS factors, in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
91
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 78 publications
9
91
1
Order By: Relevance
“…However, based on the exo1Δ mutational spectra and genetic interaction with REV3, we previously hypothesized that EXO1 participates in at least one MMR-independent mutation avoidance pathway [12]. In agreement with our supposition, recent studies have identified a potential role for EXO1 in the maintenance and repair of stalled replication forks [20][21][22].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, based on the exo1Δ mutational spectra and genetic interaction with REV3, we previously hypothesized that EXO1 participates in at least one MMR-independent mutation avoidance pathway [12]. In agreement with our supposition, recent studies have identified a potential role for EXO1 in the maintenance and repair of stalled replication forks [20][21][22].…”
Section: Introductionsupporting
confidence: 79%
“…In addition to the role of EXO1 in PRR proposed here, EXO1 has been implicated to function in cell cycle checkpoint, fork maintenance and fork repair pathways [20][21][22]51,52]. EXO1 has been shown to play subtle roles in end-processing for mitotic recombination and function redundantly with at least one other unidentified nuclease.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Consistent with these biochemical findings, it has been shown that Msh2 and Ercc1-Xpf act cooperatively in human cells to remove cisplatin ICLs and that these proteins interact as determined by co-immunoprecipitation experiments (22). Furthermore, recent findings in budding yeast have implicated a role for Msh2 and Exo I in repair of nitrogen mustard ICLs (23). Taken together these findings suggest that mismatch repair factors and Ercc1-Xpf are involved in a novel pathway of ICL repair.…”
supporting
confidence: 73%
“…In yeast and mammalian cells, nucleotide excision repair (NER), recombination, and translesion synthesis, as well as certain mismatch repair proteins, have been reported to participate in ICL repair [2,[5][6][7][8][9][10]. Recombinational repair is in part thought to be a response to formation of double-strand breaks (DSBs) at ICL that appear to be unique to eukaryotes and that arise either as a result of collapsed replication forks blocked at ICL, or as true repair intermediates [8,9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%